2014
DOI: 10.1371/journal.pone.0115260
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac Mechanics and Ventricular Twist by Three-Dimensional Strain Analysis in Relation to B-Type Natriuretic Peptide as a Clinical Prognosticator for Heart Failure Patients

Abstract: BackgroundThree dimensional (3D) echocardiography-derived measurements of myocardial deformation and twist have recently advanced as novel clinical tools. However, with the exception of left ventricular ejection fraction and mass quantifications in hypertension and heart failure populations, the prognostic value of such imaging techniques remains largely unexplored.MethodsWe studied 200 subjects (mean age: 60.2±16 years, 54% female, female n = 107) with known hypertension (n = 51), diastolic heart failure (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
4
0
4
Order By: Relevance
“…It results from the increased stress developed on the ventricular walls during systole, is distinguished by the parallel addition of new sarcomeres, and is observed in patients with LV pressure overload (usually hypertension and aortic stenosis) . Myocardial imaging studies have demonstrated that, in HFpEF, LV myocardial longitudinal and circumferential strain are decreased, whereas LV twist may be increased, normal, or occasionally decreased . The fact that LV myocardial twist is usually preserved in HFpEF is indicative of preserved double helical orientation of the LV myocardial architecture and is in accordance with previous reports, which demonstrated that muscle fibre alignment remains normal in the pressure overloaded heart despite the presence of hypertrophy or the appearance of clinical failure .…”
Section: Myocardial Fibre Shortening and Ejection Fraction In Left Vesupporting
confidence: 87%
See 1 more Smart Citation
“…It results from the increased stress developed on the ventricular walls during systole, is distinguished by the parallel addition of new sarcomeres, and is observed in patients with LV pressure overload (usually hypertension and aortic stenosis) . Myocardial imaging studies have demonstrated that, in HFpEF, LV myocardial longitudinal and circumferential strain are decreased, whereas LV twist may be increased, normal, or occasionally decreased . The fact that LV myocardial twist is usually preserved in HFpEF is indicative of preserved double helical orientation of the LV myocardial architecture and is in accordance with previous reports, which demonstrated that muscle fibre alignment remains normal in the pressure overloaded heart despite the presence of hypertrophy or the appearance of clinical failure .…”
Section: Myocardial Fibre Shortening and Ejection Fraction In Left Vesupporting
confidence: 87%
“…Myocardial imaging studies have demonstrated a significant decrease in LV myocardial longitudinal and circumferential strain, as well as in LV twist in HFrEF compared with HFpEF . It is noteworthy that both in ischaemic HFrEF and DCM, besides the compromised global and regional changes in longitudinal deformation (more preserved longitudinal strain in the LV base compared to the LV apex), LV apical rotation and overall LV systolic twist are reduced resulting in a proportional decrease in LVEF .…”
Section: Myocardial Fibre Shortening and Ejection Fraction In Left Vementioning
confidence: 99%
“…Переходя к применению показателей деформации в клинической практике, важно помнить, что не всегда их отклонения обусловлены патологическим процессом. Трехмерные спекл-трекинг исследования демонстрируют снижение стрейнов с возрастом [15,18]. Кроме того, деформационные характеристики имеют гендерные различия [15,19].…”
Section: клинические семинары §unclassified
“…КЛИНИЧЕСКИЕ СЕМИНАРЫ § В исследовании S.-N. Chang и соавт. [18] описаны достоверные количественные различия показателей деформации ЛЖ при двух формах ХСН. Определенные методом трехмерной спекл-трекинг ЭхоКГ показатели для диастолической и систолической ХСН составляют: продольный стрейн (-13,65 и -9 %), циркулярный стрейн (-23,47 и -14,52 %), твист (8,32 и 4,56°) соответственно.…”
Section: изменения серой шкалы миокарда при прогрессировании хснunclassified
See 1 more Smart Citation